Endogenous differential mortality, non-contractible effort and non linear taxation - Marie-Louise Leroux (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper studies a problem of non linear taxation when individuals have different longevities resulting from a non-monetary effort (like exercising). We first present the laissez-faire and the first best. Like Becker and Philipson (1998), we find that the laissez-faire level of effort is too high compared with the first best, because individuals do not internalize the impact of survival on the return of their savings. We also claim that because of its non-monetary form, effort is not contractible. That is why we modify our framework and assume, for the rest of the paper, that effort is determined by the individual while the social planner only allocates consumptions. It turns out that, under full information, a tax on the return of annuitized savings is desirable for both types. This tax is higher for the low-survival individual. Under asymmetric information, the low-survival individual still faces a tax while the high-survival individual might now face a positive or negative tax on annuities. Interestingly, our results depend on the value of life.
Keywords: H21; H23; H55; I12; 330; Annuities; effort; differential mortality; non linear taxation; value of life; Sterblichkeit; Moral Hazard; Gesundheitsvorsorge; Sparen; Alterssicherung; Steuerprogression; Wert des Lebens; Theorie